Characteristics of fire and smoke in the natural gas cabin of urban underground utility tunnels based on CFD simulations. (March 2021) - Wang, Wenhe; Zhu, Zhengxiang; Jiao, Zeren; Mi, Hongfu; Wang, Qingsheng
Highlights: Smoke movement in urban underground utility tunnels are investigated. Effects of ventilation mode and fire source on smoke movement are analyzed. Fire in natural gas cabins is affected by ventilation significantly. Abstract: Fire is a major risk in urban underground utility tunnels. The fire and smoke spreading characteristics in natural gas cabins of urban underground utility tunnels are important for safety engineering. In this study, computational fluid dynamics (CFD) was used to investigate the fire and smoke spreading characteristics in natural gas cabins of urban underground utility tunnels, considering different mechanical ventilation modes and fire locations. The temperature distribution and visibility contours were obtained and compared between different test cases. Results show that the oxygen in a 200 m long confined natural gas cabin of an urban underground utility tunnel can only sustain fire for 2.5 min in the case of continuous gas leakage. High mechanical ventilation speeds are unfavorable for the normal operation and maintenance of the natural gas cabin in underground utility tunnels. The location of the fire source affects the temperature distribution inside the natural gas cabin and the severity of the fire development. Based on these results, it is recommended that the mechanical ventilation speed should be controlled at approximately 1.5 m/s in the natural gas cabin with a fire protection zone of 200 m. Besides, the mechanical ventilation should also be closed first at the beginning of the fire. In addition, the natural gas cabin fire can be put out by closed self-extinguishing without mechanical ventilation. This research can provide useful guidance for the smoke control design, operation and maintenance in urban underground utility tunnels.